General Electric and GE Capital - Varma, Jayanth R., (SAGE Knowledge. Cases., 2011)
The case focuses on General Electric during the financial crash of 2008 and how this caused problems for General Electric as a whole and more specifically General Electric Capital, wholly-owned financial services subsidiary of General Electric.GE and GE Capital faced the following immediate and interrelated challenges with the onset of the uncharacteristic financial crisis: (i) tackling the deep liquidity problems arisen due to its overreliance on short-term funding, (ii) addressing the solvency issues created due to its high leverage and asset quality deterioration, and (iii) maintaining the market expectations about an investment-grade borrower. In the medium-term, it might also have to restructure its combined industrial-financial portfolio to suit the evolving business and financial environment.